2011
DOI: 10.1016/j.still.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A five-year assessment of corn stover harvest in central Iowa, USA

Abstract: Sustainable feedstock harvest strategies are needed to ensure bioenergy production does not irreversibly degrade soil resources. The objective for this study was to document corn (Zea mays L.) grain and stover fraction yields, plant nutrient removal and replacement costs, feedstock quality, soil-test changes, and soil quality indicator response to four stover harvest strategies for continuous corn and a corn-soybean [Glycine max. (L.) Merr.] rotation. The treatments included collecting (1) all standing plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 38 publications
12
66
0
Order By: Relevance
“…Negative effects of corn stover harvest on Bd under no-tillage were also reported by Blanco-Canqui et al (2006, who consistently found lower structural stability and consequently an increased susceptibility to compaction. However, other studies have reported no effects of stover harvest on Bd (Karlen et al, 1994(Karlen et al, , 2011bVillamil et al, 2015). We hypothesize that leaving corn stover on the soil surface reduced Bd through a combination of effects including protection against soil compression by machinery wheel traffic as verified by Braida et al (2006), reduced axel load associated with machinery used for alfalfa production, and perhaps preservation of active organic carbon fractions involved in stabilizing soil aggregates resulted in lower average Bd values for the no-tillage treatment.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Negative effects of corn stover harvest on Bd under no-tillage were also reported by Blanco-Canqui et al (2006, who consistently found lower structural stability and consequently an increased susceptibility to compaction. However, other studies have reported no effects of stover harvest on Bd (Karlen et al, 1994(Karlen et al, , 2011bVillamil et al, 2015). We hypothesize that leaving corn stover on the soil surface reduced Bd through a combination of effects including protection against soil compression by machinery wheel traffic as verified by Braida et al (2006), reduced axel load associated with machinery used for alfalfa production, and perhaps preservation of active organic carbon fractions involved in stabilizing soil aggregates resulted in lower average Bd values for the no-tillage treatment.…”
Section: Resultsmentioning
confidence: 53%
“…Corn stover has been identified as a potential feedstock for biofuel production because of its high cellulosic content, large volume of production and generally wide availability (Karlen et al, 2011b in the USA and other countries around the world. However, as the amount of corn stover left on the soil surface is diminished, organic C inputs are reduced, which over the time can potentially decrease soil organic matter -SOM (Karlen et al, 2011a;Jin et al, 2015) and thus affect soil structure formation and stability (Six et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Yields were adjusted to a constant water content of 155 g kg −1 for comparison among studies. Stover yields were also determined in several different ways including (1) collecting samples from a 2-m length of row and fractionating the biomass into (a) plant parts above the ear shank, (b) below the ear shank, (c) cobs, and (d) grain; (2) attaching a canvas tarp to a commercial-scale combine to collect all residue from each plot, weighing all of the residue, and then dividing and returning a portion to each plot to create removal rates of 0, 50, or 100 % of the biomass; (3) harvesting with a single-pass combine designed to simultaneously collect grain and stover [15]; (4) collecting stover with a Hesston Stackhand 1 after combining the grain; or (5) collecting stover with a commercial fail chopper after combining the grain. Stover mass was calculated using dry weights from the hand samples, or for the mechanically collected material, it was determined by weighing, subsampling, and drying a representative sample to a constant weight, so that the quantities of stover removed could be compared among sites at a water content of 0 g kg −1 .…”
Section: Methodsmentioning
confidence: 99%
“…However, the decision to harvest corn stover for bioenergy or bioproduct development is not that simple, because stover also supports many ecosystem services [12][13][14] and its harvest will increase annual nutrient removal [15][16][17]. Several reviews [e.g., 18] and workshops (e.g., www.swcs.org/roadmap) have stressed the importance of corn stover for protection against wind and water erosion, improving soil aggregation and structure, increasing infiltration and water retention, and mitigating soil temperature fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Mourtzinis et al [69] showed that harvesting the above-ear corn plant fraction, while leaving the remaining stover in the field for soil erosion protection and soil organic matter maintenance, is a potential option for corn stover harvest in the Southeast. Other research concluded that harvesting the upper half of standing stover with cobs produced the highest quality feedstock and maintained soil productivity as determined by the soil management assessment framework (SMAF) [70,71]. Total precipitation and average air temperature during the growing season were strongly correlated with stover chemical composition, and the above ear portion of stover was more desirable due to lower lignin and higher cellulose content [72].…”
Section: Corn Stover Removalmentioning
confidence: 99%